Factors Affecting Gen Z Work Performance: Case Study From E-Commerce Industry in Jabodetabek - Prasetyaningtyas, Sekar; Natalia, Cynthia; Utami, Triayu (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The objectives of this research were: to find out the influence of leadership on employee motivation in Generation Z, to determine the effect of job characteristics on employee motivation in Generation Z, to determine the effect of the work environment on employee motivation in Generation Z, to determine the effect of employee motivation on employee performance in Generation Z, to find out the influence of leadership on employee performance mediated by employee motivation in Generation Z, to determine the effect of job characteristics on employee performance mediated by employee motivation in Generation Z, to determine the effect of the work environment on employee performance mediated by employee motivation in Generation Z. A quantitative approach was used. Data were analyzed using the SEM-PLS method with SmartPLS 3 software. The variables used are leadership, job characteristics, and work environment as independent variables. Meanwhile, work performance is the dependent variable, and work motivation is the mediating variable. This study indicates that leadership, job characteristics, and work environment positively and significantly influence employee motivation. The effect of employee motivation on employee performance is also positive and significant. In addition, leadership, job characteristics, and work environment positively and significantly affect employee performance. Altogether with employee motivation as a mediating variable in Generation Z. The conclusion of this study shows that the three independent variables (leadership, work characteristic, and work environment) have a positive and significant effect on the dependent variable (work performance), including the mediating effect of work motivation. Keywords: leadership, job characteristics, work environment, employee performance, employeemotivation